Assessment of Visual Acuity in Children Using Crowded Lea Symbol Charts. Issue 8 (August 2018) - Sailoganathan, Ananth; Rou, Leong Xin; Buja, Kenny Anak; Siderov, John
Abstract : SIGNIFICANCE: Vision charts comprising single Lea symbols surrounded by either flanking bars or flanking Lea symbols are available for measurement of visual acuity in children. However, the results obtained with such charts may not be interchangeable owing to potential differences in the crowding effect. PURPOSE: The purpose of this study was to compare habitual visual acuity in a sample of young children using two versions of the single Lea symbols charts with different crowding features. METHODS: Monocular habitual visual acuity was measured in a sample of 77 young children aged between 4 and 6 years using crowded Lea symbols charts with either flanking bars separated from the central symbol by 0.5 optotype width or flanking Lea optotypes separated from the central symbol by 1.0 optotype width. RESULTS: Mean visual acuity was higher (i.e., lower logarithm of the minimum angle of resolution) with the Lea symbols crowded using flanking optotypes, equivalent to about 1.5 optotype difference. Visual acuity measured with the two charts was significantly correlated; however, the 95% limits of agreement were larger than expected from repeatability studies using Lea symbols. CONCLUSIONS: Lea symbols with flanking optotypes resulted in higher visual acuity than the Lea symbols with flanking bars, probably as a result of differences in the crowding effect. The two charts showed insufficient agreement, and we do not recommend their use interchangeably. We recommend using the Lea symbols with flanking bars because of the closer flanker-target separation.